Levels of serum copper and zinc in healthy adults from the west of Algeria - Attar, Tarik (SPC Journal of Environmental Sciences, 2019)
Essential trace element include zinc (Zn) and copper (Cu) are essential elements that play an important role in the whole-body metabolism. They have been implicated to play important roles in immuno-physiologic functions. The concentration of these elements in human organism varies widely between geographical areas depending on its content in soil and plants, dietary intake, bioavailability and retention, mineral interactions and other factors. The aim of this study was to measure the alterations in serum trace element concentrations, including Zn and Cu in one hundred and fifteen healthy adults (fifty-two males and sixty-three females) living in the west of Algeria using differential pulse anodic stripping voltammetry (DPASV) on a hanging mercury drop electrode. The mean copper and zinc concentrations were 105.26Â±19.63 Î¼g/dL and 79.44Â±10.28 Î¼g/dL, respectively. Serum concentrations of these elements were in the same range as those found for populations of other European countries.Â